SCIENTOMETRIC ANALYSIS OF ELECTRICAL MODALITIES IN KNEE REHABILITATION (1983-2023) - MANAF, HAIDZIR; MAZEHI, NAZRIN; AZHAR, NOOR IZZATI; MOHD NOOR, MOHD IQBAL; MD NOR, NORAZMIR; MUNAJAT, MUNAYATI; AZIZAN, AZLIYANA; MOHD ASMAWI, UMMI MOHLISI; BUKRY, SAIFUL ADLI (International Journal of Allied Health Sciences, 2025)
Introduction: Electrical modalities represent a therapeutic modality employed in rehabilitation settings aimed at augmenting or facilitating the recovery of individuals afflicted with diverse neurological or musculoskeletal diseases. This intervention requires the application of electrical currents to targeted regions of the body, typically administered via electrodes positioned on the skin, with the intent of eliciting physiological responses and fostering therapeutic benefits. An examination of its trajectory through various analytical lenses, such as bibliometrics, underscores the imperative of comprehending its global ramifications. In recent years, scientometric investigations have emerged as interactive methodologies for evaluating the performance of specific domains of inquiry. These inquiries yield interactive visualizations and figures, affording insights into multifaceted aspects of information. Moreover, scientometric research equips scholars with tools to synthesize evidence gleaned from literature amassed in scientific repositories. Method: The inception of the Web of Science (WOS) database in 1983 has facilitated the aggregation of scientific publications, revealing a discernible uptrend in research pertaining to electrical modalities for knee rehabilitation from 1983 to 2023. This study endeavors to delineate the contemporary landscape of research surrounding electrical modalities for knee rehabilitation through scientometric analysis. Result: The progression of scientific publications in this domain demonstrates a consistent upward trajectory. While the volume of publications was inadequate in 1983, comprising merely one paper, this figure surged dramatically, reaching 80 publications by 2019. Furthermore, these publications collectively garnered a substantial citation count of 19,660, precipitating the identification of 27 co-citation clusters through cluster analysis. Conclusion: The realm of electrical modalities for knee rehabilitation emerges as a promising frontier for scholarly inquiry. The escalating trajectory of research publications, coupled with the considerable citation impact, underscores the significance and prospective advancements within this sphere.